Adaptation of personality questionnaire effective in high school students in state educational centers - Bulnes B., Mario (2014)
The main objective of this paper is to present the adaptation of effective personality questionnaire in high school students in state educational centers of Lima city. The theoretical construct of effective Personality instrument was developed by Martin del Buey (1997, 2000) in an attempt to describe and explain the personal factors that affect the performance of students in the secondary education level. The original instrument was developed by Fernández, Moris, Marcone, Wheat and Dapelo. The sample used consists of 377 students, aged between 14 and 17 years, of which 173 are female and 204 male, fourth and fifth grade. The results show that Martin del Buey´s effective personality questionnaire has construct validity, assessed through exploratory factor analysis extracting the presence of four factors or constructs, which have internal consistency estimates for the reliability indices.